SO CLOSE, YET SO FOREIGN: AUSTRALIANS’ AMBIVALENT VIEW TOWARDS INDONESIA IN THREE POEMS - Eko Rujito Dwi Atmojo; Ariva Luciandika (Universitas Negeri Yogyakarta, 2023)
Literary works embody writers’ view, which is undoubtedly a product of their cultural background and values. Thus, when a western writer writes about eastern themes, his values and worldview as westerner might influence his view towards the East. In the case of Australian writers writing about Indonesia, this notion proves to be problematic. Australians’ ambivalent identity as a people and the stark contrast in sociological, cultural, and historical as well as unique relation between the two countries often result in ambivalence in their view towards Indonesia. Applying postcolonial criticism, this study was endeavoured to uncover Australians’ ambivalent view towards Indonesia portrayed in three poems about Indonesia written by Australian writers. Descriptive-qualitative analysis on the poems revealed that there are ambivalences in how Australians view Indonesia which transcend the dichotomy between the Occident and the Orient. Australians see Indonesia as ‘other’ and at the same time acknowledge the differences and diversities as part of universal reality.